The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/foods12112167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermosonication on Amino Acids, Phenolic Compounds, Sensory Properties and Microbial Quality in Freshly Squeezed Verjuice

Abstract: Thermosonication is a process that can be used as an alternative to thermal pasteurization by combining mild temperature and ultrasound treatments. This study evaluated the effects of verjuice on the thermosonication process and its bioactive values modeled with the RSM (response surface method). The bioactive components of verjuice were found to increase with high predictive values. Additionally, the presence and amounts of 20 free amino acids in C-VJ (untreated verjuice), P-VJ (thermally pasteurized verjuice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
1
3
2
Order By: Relevance
“…The retention of a significant amount of AA may be due to the removal of confined molecules of oxygen during the TS treatment of juices. 3,36 This finding is consistent with research on thermosonicated juice made from amora and citrus fruits, which was done concurrently. 16,34 Additionally, the decrease in AA content at higher temperatures and prolonged exposure periods may be attributed to the generation of oxidative radicals under intense sonolysis effects, a phenomenon previously documented in hog plum juice.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The retention of a significant amount of AA may be due to the removal of confined molecules of oxygen during the TS treatment of juices. 3,36 This finding is consistent with research on thermosonicated juice made from amora and citrus fruits, which was done concurrently. 16,34 Additionally, the decrease in AA content at higher temperatures and prolonged exposure periods may be attributed to the generation of oxidative radicals under intense sonolysis effects, a phenomenon previously documented in hog plum juice.…”
Section: Resultssupporting
confidence: 85%
“…Phenolic compounds can act as antioxidants, and their preservation is favored under conditions of reduced oxidative stress. 36…”
Section: Resultsmentioning
confidence: 99%
“…The TS-POJ process (10.49 ± 0.20 mg/100 mL) resulted in a smaller reduction in ascorbic acid content compared to the P-POJ process (9.52 ± 0.36 mg/100 mL). In contrast to the results in our study, Çöl et al (2023) found in their research that there was no statistically significant decrease in the ascorbic acid value in sour cherry juice compared to the control sample after the application of thermal pasteurization and thermosonication processes [8]. In a study conducted by Putsakum et al (2023), the effect of thermosonication on antioxidant compounds in blackberry juice was investigated.…”
Section: Ascorbic Acid Activitiescontrasting
confidence: 98%
“…In many studies, it was determined that bioactive components increase in foods and beverages [5]. Furthermore, there is various research in the literature showing that ultrasound technology enriches the quality of juice, with examples including black carrot juice [6], fresh pomegranate juice [7], fresh verjuice [8], posotia (Vitex negundo) juice [9] and beetroot (Beta vulgaris L.) juice [10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, with the ultrasound technique, among the novel non-thermal technologies increasingly utilized today, the product’s loss of flavor and taste is minimal. In contrast, the product’s nutritional value is enhanced [ 23 , 24 , 25 , 26 , 27 ]. Ultrasound treatment and thermal pasteurization positively affect the antioxidant and phenolic content of fruit, fruit juices, and vinegar [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%